Pengaruh Pertanyaan Pemantik Terhadap Kemampuan Bernalar Kritis dan Hasil Belajar Peserta Didik - Pandu, Respati; Purnamasari, Iin; Nuvitalia, Duwi (Pena Edukasia, 2023)
The background that drives this research is that the learning process is not optimal in training critical thinking skills so that it affects learning outcomes which are still low. The aims of this study were 1) to find out the effect of triggering questions on students' critical reasoning abilities. 2) Measuring the influence of trigger questions on student learning outcomes. This type of research is quantitative in the form of a true experimental design with a pretest posttest control group design. Based on the analysis of the results of the learning completeness test and the comparative test, it shows that the critical reasoning ability of the experimental class using questions from the classical percentage is 73%. The average post-test score was 70.2 and the classical percentage control class was 20% and the average post-test score was 54.9 with minimum completeness criteria (MCC) 65, obtained tcount 3.108 and ttable 1.701 with a significant level of 0.05 and dk = 15+15 - 2 = 28 tcount 3.108 > ttable 1.701, so Ho is rejected and Ha is accepted. So it can be concluded that there is a significant influence on critical reasoning abilities and learning outcomes of students in the experimental class compared to the control class, in social studies and science subjects, Theme 7 Sub-theme 1.